2018
DOI: 10.1111/cpr.12503
|View full text |Cite|
|
Sign up to set email alerts
|

Tetrahedral DNA nanostructures facilitate neural stem cell migration via activating RHOA/ROCK2 signalling pathway

Abstract: In conclusion, TDNs could enter NSCs without the aid of other transfection reagents in large amounts, whereas only small amounts of ssDNA could enter the cells. TDNs taken up by NSCs activated the RHOA/ROCK2 signalling pathway, which had effects on the relevant genes and proteins expression, eventually promoting the migration of NE-4C stem cells. These findings suggested that TDNs have great potential in application for the repair and regeneration of neural tissue.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 52 publications
(42 citation statements)
references
References 61 publications
1
41
0
Order By: Relevance
“…Thus, the combination of aptamers and DNA tetrahedrons lays the foundation for targeted drug delivery and next-generation treatments. Our results showed that the TDN could enter cells without transfection agents, which is similar to the results of Walsh et al and Ma et al [ 15 , 19 ]. Compared with that of the TDN, uptake of the Apt-TDN by U87MG cells was significantly increased.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Thus, the combination of aptamers and DNA tetrahedrons lays the foundation for targeted drug delivery and next-generation treatments. Our results showed that the TDN could enter cells without transfection agents, which is similar to the results of Walsh et al and Ma et al [ 15 , 19 ]. Compared with that of the TDN, uptake of the Apt-TDN by U87MG cells was significantly increased.…”
Section: Discussionsupporting
confidence: 92%
“…Research has shown that ANG-TDN can cross the BBB. Ma et al [ 19 ] suggested that tetrahedral DNA nanostructures can enter neural stem cells (NSCs) without the need for transfection agents, where they promote neural stem cell migration, proliferation, and differentiatio n[ 20 ], and have great potential for neural tissue repair and regeneration. Therefore, we investigated the possibility of the use of TDN in glioma therapy and enhancing its targeting ability.…”
Section: Introductionmentioning
confidence: 99%
“…The specific synthesis details of tFNAs can be seen in previous research reports [ [26] , [27] , [28] ]. S1–S4 single DNA strands - Table 1 showed the sequence of bases for each strand of DNA.…”
Section: Methodsmentioning
confidence: 99%
“…To confirm the successful synthesis of As-TDN-R, 3% agarose gel was used to separate each of the DNA samples based on their migration speed. 22 As shown in Figure 1A, the first four bands represented four single-strand DNA (Lane 1: As-s1, Lane 2: si-s2, Lane 3: s3, Lane 4: s4). Due to external modification, band 1 and band 2 moved slowly compared with Scheme 1 Schematic illustration for the synthesis of As-TDN-R. Aptamer AS1411 is linked on the strand of s1 for selective delivery into the glioma cells.…”
Section: Dovepressmentioning
confidence: 99%